Outdoor games and athletic exercises as a means of increasing the speed capabilities of pupils of secondary school age - Zubov Evgenij Viacheslavovich; Trofimov Vladimir Anatolievich (Kharkov National Pedagogical University, 2011)
Considered playing techniques of organizing and conducting physical education lessons. Was examined 79 healthy students 6-7 classes (boys and girls). Recommended to apply the lessons systematically moving games and relay races. The positive influence on the formation of the lessons of sustainable interest in physical training. It is recommended up to 50% of the time take a lesson playing exercises and relays. It is established that running and jumping exercises should be targeted, variation, varied influence on the development of high-speed capabilities of schoolchildren. This technique of lessons promotes the harmonious development of students, the growth of other indicators of physical fitness and health.